CONSUMER BEHAVIOR ANALYSIS IN MAXIMUM SATISFACTION: CASE STUDY ON STUDENTS IN FULFILLING THEIR NEEDS - Kusumawati, Ririn; Rahmi, Rosida Mutia (Edunomika Journal : Studies In Education And Development Economics, 2026)
This study aims to analyze student consumer behavior in achieving maximum satisfaction through an ordinal approach. The main focus of this study is to evaluate how the combination of consumption of academic support goods (books, stationery, photocopying) and basic necessities (food, internet, transportation) interacts with budget constraints in forming consumer equilibrium. Using a descriptive quantitative method, this study involved 108 students of Economics Education, class of 2016, at the University of Jambi, as respondents selected through proportional random sampling technique. Data were analyzed using linear regression and the application of the Lagrange function to determine the optimal point of satisfaction. The results showed that simultaneously, the combination of consumed goods significantly influenced the level of student satisfaction, with food and internet as the most dominant determinants. Empirical findings identified that the point of maximum satisfaction was achieved at a combination of internet consumption of 1,783 GB and food of 1,030 portions per year with a total budget of IDR 11,585,622. The novelty of this study lies in the application of ordinal utility theory to dissect the specific consumption patterns of prospective economics education students, which revealed a shift in priorities from physical literature to digital access. The implications of this research contribute to the development of microeconomics, particularly consumer behavior theory, by providing empirical evidence regarding the "survival equilibrium" among college students. In the field of economics education, these results emphasize the importance of strengthening financial literacy so that students can allocate resources more productively. Educational institutions can use these findings as a policy basis for providing more affordable access to digital literacy to align consumption realities with ideal academic needs.